2015
DOI: 10.1242/dev.123059
|View full text |Cite|
|
Sign up to set email alerts
|

Reck enables cerebrovascular development by promoting canonical Wnt signaling

Abstract: The cerebral vasculature provides the massive blood supply that the brain needs to grow and survive. By acquiring distinctive cellular and molecular characteristics it becomes the blood-brain barrier (BBB), a selectively permeable and protective interface between the brain and the peripheral circulation that maintains the extracellular milieu permissive for neuronal activity. Accordingly, there is great interest in uncovering the mechanisms that modulate the formation and differentiation of the brain vasculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 143 publications
(196 reference statements)
2
44
0
2
Order By: Relevance
“…In mice, Reck plays an essential role in embryonic and placental vascular remodeling, and these activities have been ascribed to its function as an MMP inhibitor, with at least one site of action in pericytes (Oh et al, 2001; Chandana et al, 2010; de Almeida et al, 2015). In zebrafish, loss-of-function Gpr124 and Reck mutations have very similar phenotypes, with each gene playing an essential role in the development of dorsal root ganglia and intracerebral vascularization (Prendergast et al, 2012; Vanhollebeke et al, 2015; Ulrich et al, 2016). In cell culture, Gpr124 and Reck strongly enhance Frizzled- and Lrp5/6-dependent canonical Wnt signaling by Wnt7a and Wnt7b, but not by any of the other 17 mammalian Wnts or by Norrin, and in mice the Gpr124 knockout phenotype can be rescued by experimentally activating canonical Wnt signaling (Zhou and Nathans, 2014; Posokhova et al, 2015; Vanhollebeke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Reck plays an essential role in embryonic and placental vascular remodeling, and these activities have been ascribed to its function as an MMP inhibitor, with at least one site of action in pericytes (Oh et al, 2001; Chandana et al, 2010; de Almeida et al, 2015). In zebrafish, loss-of-function Gpr124 and Reck mutations have very similar phenotypes, with each gene playing an essential role in the development of dorsal root ganglia and intracerebral vascularization (Prendergast et al, 2012; Vanhollebeke et al, 2015; Ulrich et al, 2016). In cell culture, Gpr124 and Reck strongly enhance Frizzled- and Lrp5/6-dependent canonical Wnt signaling by Wnt7a and Wnt7b, but not by any of the other 17 mammalian Wnts or by Norrin, and in mice the Gpr124 knockout phenotype can be rescued by experimentally activating canonical Wnt signaling (Zhou and Nathans, 2014; Posokhova et al, 2015; Vanhollebeke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whether canonical Wnt signaling also regulates the gradual suppression of transcytosis is not clear. On one hand, recent studies demonstrated canonical Wnt signaling is essential in the tip cells of nascent sprouts (Ulrich et al, 2016; Vanhollebeke et al, 2015) yet these nascent, distal vessels display bulk transcytosis and lack Mfsd2a during BRB development. But on the other hand, microarray analysis on retinas from canonical Wnt signaling deficient mice showed that Mfsd2a is downregulated (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, biochemical evidence for this concept is largely lacking. TSPAN12 (tetraspanin family) and GPR124 (adhesion GPCR family) have distinct structures and characteristics, e.g., GPR124 appears to function together with another membrane molecule, RECK (Ulrich et al, 2016; Vanhollebeke et al, 2015). Available crystal structures of NDP in complex with the extracellular domain of FZD4 show that a NDP head-to-tail dimer contacts two FZD4 molecules (Chang et al, 2015; Shen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%